Ordinary and Special Regimes of electricity generation in Spain: How they interact with economic activity - Marques, António Cardoso (2019)
The purpose of this paper is to review the literature focused on the energy/electricity-growth nexus, highlighting how the focus has shifted from aggregated energy/electricity consumption towards specific energy sources. Moreover, it aims to shed light on the relationships between different energy/electricity sources and economic growth. Empirically, the paper focuses on the analysis of interactions between electricity generation in Spain under both the Special Regime (SR) and the Ordinary Regime (OR), and their relationship with economic activity. Data for Spain is studied for a time span from January 2003 to January 2016. The Toda-Yamamoto causality test is carried out to check for causality relationships. Additionally, both short- and long-run effects are assessed by using the ARDL bounds test approach. Overall, the results reveal high internal consistency when comparing the ARDL results with the causality analysis. The substitution effect was detected between OR and SR. However, the negative effect of the SR on economic activity deserves special attention by energy policymakers.This paper argues that the main challenge of renewable sources for policymakers is their cost-effectiveness.